Discovery, Analysis, and Elimination of Instantaneous Misfires in Underground Production Blasts (2000 International Society of Explosives Engineers) - David B. Counter; Norman Disley; Lionel Hebert (International Society of Explosives Engineers, 1996)
Misfires in underground and surface production blasts can be costly. Costs can arise from loss of resource, production interruptions, having to redrill or otherwise refire the blast (a hazardous process at best), due to added secondary blasting or breakage, and/or from increased LHD maintenance costs attributable to poor fragmentation.